2012
DOI: 10.1111/j.1469-0691.2012.03951.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hepatitis B virus drug-resistant mutant haplotypes by ultra-deep pyrosequencing

Abstract: Direct sequencing and reverse hybridization are currently the main methods for detecting drug-resistance mutations of hepatitis B virus (HBV). However, these methods do not enable haplotype analysis so they cannot be used to determine whether the mutations are co-located on the same viral genome. This limits the accurate identification of viral mutants that are resistant to drugs with a high genetic barrier. In our current study, ultra-deep pyrosequencing (UDPS) was used to detect HBV drug-resistance mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…Because (1) several studies concordantly demonstrated high reliability and reproducibility of 454 technology for variants >1%, [18][19][20] and (2) serial dilution experiments (see supplemental Methods for details) confirmed the ability of our assay to detect mutations as low as 1% (whereas lower levels were not investigated), we decided to reduce the likelihood of false-positive results by filtering-out variants with ,1% abundance and to exploit high coverage only for haplotype and clonal evolution analyses.…”
Section: Uds Of the Bcr-abl Kdmentioning
confidence: 89%
“…Because (1) several studies concordantly demonstrated high reliability and reproducibility of 454 technology for variants >1%, [18][19][20] and (2) serial dilution experiments (see supplemental Methods for details) confirmed the ability of our assay to detect mutations as low as 1% (whereas lower levels were not investigated), we decided to reduce the likelihood of false-positive results by filtering-out variants with ,1% abundance and to exploit high coverage only for haplotype and clonal evolution analyses.…”
Section: Uds Of the Bcr-abl Kdmentioning
confidence: 89%
“…The newly available ultradeep pyrosequencing (UDPS) technique, currently the most competitive for mass spectrometry, detects HBV drug-resistant strains in plasma samples if they show HBV DNA levels Ն10 3 IU/ml, which is 10 times higher than those detected using MALDI-TOF MS. Moreover, several drug resistance mutations were detected at frequencies of Ͼ1% (40,41). Thus, high-throughput MALDI-TOF MS provides an alternative approach to HBV genotyping.…”
Section: Discussionmentioning
confidence: 99%
“…Haplotyping can provide details regarding viral subpopulation complexity. This may be useful for antiviral resistance requiring multiple mutations (e.g., Entecavir), though they may predominantly colocalize to the same viral genome (27). Further study is needed to determine whether there is a clinical effect of differentiating patients with mutations present (that may or may not colocalize to the same viral genome) as tested by LiPA or Sanger sequencing compared to patients with mutations localized to a predominant haplotype (NGS).…”
Section: Discussionmentioning
confidence: 99%